Research on indirect cooling for photovoltaic panels based on radiative cooling. (October 2022) - Li, Shuai; Zhou, Zhihua; Liu, Junwei; Zhang, Ji; Tang, Huajie; Zhang, Zhuofen; Na, Yanling; Jiang, Chongxu
Abstract: Radiative cooling (RC) is a passive cooling technology that has been used to cool photovoltaic (PV) panels since it does not consume energy or produce pollution. Previous studies employed RC materials above the PV panels to directly enhance the thermal emission, thereby lowering the temperature, but this method interfered with the absorption of the sunlight simultaneously, and thus reduced the power conversion efficiency (PCE). In this paper, an indirect cooling system for PV panels based on RC was proposed, consisting of the PV module, RC module, cold storage module, and piping system. The RC module was arranged between the adjacent PV panels, and the generated cold energy was used to cool the PV panels through the water system. Experimental results showed that the system without cold storage module reduced the average temperature of PV panels by 13.6 °C and 10.6 °C respectively in summer and autumn, and increased the PCE by 1.21% and 0.96%, respectively. After employing the cold storage, the cold energy generated at night by the RC module was stored for daytime use, then the average temperature of PV panels was reduced by 17.8 °C and 16.6 °C in summer and autumn, and the PCE was increased by 1.69% and 1.51%, respectively. Moreover, a cover shield and large water tank capacity could further improve the system efficiency. In addition, the proposed system has an economic payback period of 8 years and is expected to increase at least 2.8 billion kWh of PV power generation in 2050. Highlights: An indirect cooling system for PV panels based on radiative cooling was proposed. The average temperature was reduced by 17.8 °C, and the PCE was increased by 1.69%. A cold storage module was used to further improve the cooling performance. The employment of cover shield and the volume of the water tank were discussed. The economic payback period is 8 years.